(untitled) (ItalianoLinguadue, 2023)
Questo contributo descrive i repertori linguistici degli italiani migrati stanziati a Toronto (Canada) e a Londra (Regno Unito); propone di mostrare la loro evoluzione nel corso delle diverse ondate migratorie, in modo da individuare somiglianze e divergenze tra i flussi degli anni Cinquanta e Sessanta e le migrazioni contemporanee. In tale prospettiva, obiettivo ultimo del contributo è evidenziare la criticità della nozione di heritage langauge così come applicata allo studio delle comunità italiane nel mondo e di suggerire modelli di lettura alternativi basati al concetto di repertorio linguistico. Parallelisms and discontinuities in two anglophone contexts This paper focuses on the linguistic repertoires of Italian migrants settled in two different cities, that are Toronto (in Canada) and London (in the UK). It aims to show their evolution during the various migratory waves and to identify similarities and differences between the flows that took place in the Fifties and in the Sixties and those that started after the recent crisis. The ultimate goal of the paper is to highlight the critical points of the heritage language approach as applied to the study of Italian communities worldwide: the paper aims of discuss alternative approaches based on the notion of linguistic multiple repertoire that has been recently proposed by several authors.